Low temperature gas phase reaction rate coefficient measurements: Toward modeling of stellar winds and the interstellar medium. Issue Volume 15:Issue S350(2019) (April 2019) - West, Niclas A.; Rutter, Edward; Blitz, Mark A.; Decin, Leen; Heard, Dwayne E.
Abstract: Stellar winds of Asymptotic Giant Branch (AGB) stars are responsible for the production of ∼85% of the gas molecules in the interstellar medium (ISM), and yet very few of the gas phase rate coefficients under the relevant conditions (10 – 3000 K) needed to model the rate of production and loss of these molecules in stellar winds have been experimentally measured. If measured at all, the value of the rate coefficient has often only been obtained at room temperature, with extrapolation to lower and higher temperatures using the Arrhenius equation. However, non-Arrhenius behavior has been observed often in the few measured rate coefficients at low temperatures. In previous reactions studied, theoretical simulations of the formation of long-lived pre-reaction complexes and quantum mechanical tunneling through the barrier to reaction have been utilized to fit these non-Arrhenius behaviours of rate coefficients. Reaction rate coefficients that were predicted to produce the largest change in the production/loss of Complex Organic Molecules (COMs) in stellar winds at low temperatures were selected from a sensitivity analysis. Here we present measurements of rate coefficients using a pulsed Laval nozzle apparatus with the Pump Laser Photolysis - Laser Induced Fluorescence (PLP-LIF) technique. Gas flow temperatures between 30 – 134 K have been produced by the University of Leeds apparatus through the controlled expansion of N2 or Ar gas through Laval nozzles of a range of Mach numbers between 2.49 and 4.25. Reactions of interest include those of OH, CN, and CH with volatile organic species, in particular formaldehyde, a molecule which has been detected in the ISM. Kinetics measurements of these reactions at low temperatures will be presented using the decay of the radical reagent. Since formaldehyde and the formal radical (HCO) are potential building blocks of COMs in the interstellar medium, low temperature reaction rate coefficients for their production and loss can help to predict the formation pathways of COMs observed in the interstellar medium.